A Comparative Content Analysis of News Stories and Press Releases During the 2015 Blue Bell Ice Cream Recall - Brandyl Brooks Calley; Courtney Meyers; Courtney Gibson; Erica Irlbeck (Journal of Applied Communications, 2019)
In 2015, Blue Bell Creameries had its first recall in the company’s history. Blue Bell issued a voluntary recall of all of its ice cream products after Listeria was detected and was linked to 10 illnesses that resulted in three deaths. With the theoretical framework of framing and Situational Crisis Communication Theory, the purpose of this study was to explore how this recall was presented in company press releases and news media coverage to determine what crisis communication strategies Blue Bell implemented and how the media presented that information. This study was a content analysis of 23 press releases from Blue Bell and 68 articles from newspapers. The four crisis response strategies, or postures, used as frames were deny, diminish, rebuild, and bolster. This study also examined sources identified in the articles and the topic areas they discussed. The results indicated Blue Bell’s communication efforts were properly and effectively disseminated through the news media to the public. Blue Bell used accommodative crisis communication postures to restore its reputation. Blue Bell was also commonly found as a source in the news stories, which benefitted the company when communicating about the recall to the public. This study provided an examination of crisis communication strategies and reputation management for organizations related to one specific food recall, which should encourage additional studies of these strategies in food and agricultural industries.
Keywords: crisis communication; crisis response strategies; Blue Bell; food recall; content analysis